2012
DOI: 10.1007/978-3-642-35362-8_31
|View full text |Cite
|
Sign up to set email alerts
|

Sophisticated Phishers Make More Spelling Mistakes: Using URL Similarity against Phishing

Abstract: Abstract. Phishing attacks rise in quantity and quality. With short online lifetimes of those attacks, classical blacklist based approaches are not su cient to protect online users. While attackers manage to achieve high similarity between original and fraudulent websites, this fact can also be used for attack detection. In many cases attackers try to make the Internet address (URL) from a website look similar to the original. In this work, we present a way of using the URL itself for automated detection of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In this section we focus on work which looks at deceiving people with malicious URLs. Numerous studies have shown that people have trouble accurately identifying phishing URLs [14,31,11,15]. Users are generally more likely to draw clues from the page that has been loaded than from the URL or other security indicators [14,4,28,2].…”
Section: Phishingmentioning
confidence: 99%
“…In this section we focus on work which looks at deceiving people with malicious URLs. Numerous studies have shown that people have trouble accurately identifying phishing URLs [14,31,11,15]. Users are generally more likely to draw clues from the page that has been loaded than from the URL or other security indicators [14,4,28,2].…”
Section: Phishingmentioning
confidence: 99%
“…The deceptions are simple, yet effective. This has attracted considerably high attention from the anti-phishing researchers to focus on a URL-based approach (Maurer and Höfer, 2012). Nguyen et al (2013) and Verma and Dyer (2015) are among the works that contribute to the URL-based approach.…”
Section: Related Workmentioning
confidence: 99%
“…Nguyen et al (2013) and Verma and Dyer (2015) are among the works that contribute to the URL-based approach. An interesting one is Maurer and Höfer (2012) which uses spelling recommendations from a search engine and a string similarity algorithm. Since each URL is unique, phishers can only use small spelling mistakes that might go overlooked by unsuspecting users to impersonate a legitimate URL.…”
Section: Related Workmentioning
confidence: 99%
“…Anti-phishing techniques for the web have been deployed in practice [7,16]. Proposals include automated comparison of website URLs [27], visual comparison of website contents [4,43], use of a separate and trusted authentication device [30], personalized indicators [6,20,33], multi-stage authentication [14], and attention key sequences to trigger security checks on websites [41]. While some of these mechanisms are specific to the web environment, others could be adapted also for mobile application phishing detection.…”
Section: Related Workmentioning
confidence: 99%